Review of the regional nomenclature and tectonic setting for mesozoic gold deposits in the Malanyu Anticline area of Eastern Hebei Province, North China. Issue 18 (12th December 2021) - Bagas, Leon; Bierlein, Frank; Jiang, Si-Hong; Liu, Yi-Fei; Zhang, Li-Li
ABSTRACT: North China (NC) is a region recording a long and complex geological history spanning from the Archaean to Cenozoic. This included magmatism, sedimentation, metamorphism, and deformation, demonstrating that the region is not a craton. To date, few studies have considered the links between multiple deformation events, emplacement of granites, and the deposition of gold deposits during the Mesozoic evolution of northeastern NC coeval with deformation in the Central China Orogen. The Malanyu area is a well-exposed part of NC, where almost continuous sedimentation and multiple deformation events are recorded. Long-lived magmatism broadly extended between ca. 220 and 118 Ma and is concentrated in the hinge zone of the east-trending Malanyu Anticline, which is a large-scale anticline deformed multiple times. Timing relationships between sedimentation, deformation, and magmatism show that the structure must be between 250 and 220 Ma. The upper limit corresponds to the closure of the Palaeoasian Ocean during the onset of collision between the Central Asian Orogen and NC to the south. Magmatism in the anticline's hinge zone can be subdivided into three magmatic events between ca. 220–214, 200–143 and 128–118 Ma separated at ca. 212–202 Ma and ca. 140–130 Ma, and these periods of magmatic hiatus correspond to unconformities in the sedimentary succession. The oldest granite in the area is ca. 220 Ma limiting the age of the anticline between ca. 250 and 220 Ma. The gold mineralisation was emplaced in structurally prepared sites along faults and anticline hinge zones and broadly contemporaneous with the magmatic events. The gold assays of samples collected for this study show that the hinge zone of the Malanyu Anticline, around the intersection of the Myun-Xifengkou-Qinglong Shear Zone and Baiyangyu Fault, the area west of the Dashan Granite, and the northwestern part of the study area are prospective for gold.